New conceptual approaches to cognition in systems engineering: applying the 4 E's of cognition. Issue 6 (23rd August 2022) - Rao, Vikram M; Francis, Royce A
Abstract: This paper presents novel approaches to investigate aspects of cognition in organization and team‐based decision making. The authors draw on recent literature in team and organizational learning, cognition, behavior, knowledge management, macrocognition, and human factors to support this approach. The authors discuss five novel cognitive approaches based on this literature. The authors draw parallels with the philosophical "4E cognition" of organism model, which describes four types of cognition present in organisms. The authors note that previous literature has discussed analogous behavior between organizations and organisms, and that organizations can be described as complex systems mimicking organism structure and behavior. The authors discuss applications of these approaches in systems engineering contexts, including complex system design, decision making, and knowledge management that future research should pursue.